2018
DOI: 10.17221/107/2017-rae
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Lupinus albus axial rotary combine harvesters

Abstract: To ensure the agricultural production of the plant protein, it is advisable to cultivate leguminous crops, such as white lupine (Lupinus albus), which are rich in plant protein. White lupine is an easily threshed crop. Its seeds are large enough, so the main problem is to avoid seed damage during harvesting. To improve the harvesting technology of white lupine, the authors suggest using grain combine harvesters with axial flow threshing and separating mechanism (TSM). They consider it necessary to modify the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Therefore, after threshing the grain mass with combine harvesters [3,4,5], grain heaps contain poisonous ergot sclerotia in addition to grain, organic and mineral impurities [6,7,8]. Therefore, to obtain grain suitable for food, technical and seed purposes, it is necessary to clean the grain heap, the task of which is to isolate all impurities, especially toxic ergot.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, after threshing the grain mass with combine harvesters [3,4,5], grain heaps contain poisonous ergot sclerotia in addition to grain, organic and mineral impurities [6,7,8]. Therefore, to obtain grain suitable for food, technical and seed purposes, it is necessary to clean the grain heap, the task of which is to isolate all impurities, especially toxic ergot.…”
Section: Introductionmentioning
confidence: 99%
“…Above analyzed experiments showed that, combine harvester should be used at the suitable working regimes depending on the sort of crop, yield and grain moisture. As if like these recommendations were suggested by Pristavka and Aldoshin [19][20][21].…”
Section: Resultsmentioning
confidence: 97%
“…Currently, grain production is mechanized. Harvesting is carried out by combine harvesters [3,4,5]. After threshing the grain mass with these combines, due to the imperfection of their cleaning mechanism, the grain heap contains grain, organic and mineral impurities, as well as harmful impurities, which include poisonous ergot sclerotia [6,7,8].…”
Section: Introductionmentioning
confidence: 99%